Nanometric modeling of migration of α-Tocopherol from whey protein-based films on the cheese surface (2023)
ABSTRACT: Nanotechnology has enabled the development of active food packaging with enhanced barrier properties and size of the compounds incorporated into the material to the nanoscale alters their properties. Such interaction requires understand their migration nanoscale mechanisms to release from the material to the food. The objective of this study was to model the migration process of α-Tocopherol on a nanoscale from whey protein-based films to cheese surfaces and compare the findings with experimental data obtained from double cream cheese samples. For the experimental analyses, the whey protein-based films loaded with α-Tocopherol were stored at 4, 14, and 25 ◦C. The system (film and double cream cheese) was sampled at different time intervals for extraction, quantification of migrant, and the migration process was studied by solving the general diffusion equation of Fick’s second law. The migration of α-Tocopherol was modeled using a random walk scheme and a simplified one-dimensional model. A specific algorithm was developed for this study and utilized to model the migration process. The results confirmed the experimental migration of α-Tocopherol from the film to the cheese, yielding the respective experimental partition and diffusion coefficients at different temperatures for the active compound. Likewise, the modeling for the migration phenomenon allowed estimating the respective diffusion coefficients using the model based on Fick’s second law and special a nanometric scale through the Brownian movement. The models accurately adjusted to the experimental data, depicting the concentration of the migrant as a function of time.